The axis of the tropical easterly jet stream over India and Ceylon (MAUSAM, 1974)
Rawin observations of a number of stations for the months June to September for the five-year (1961-65) have been analysed to study the vertical structure of the tropical easterly jet stream over the Peninsular India and over the regions to the south of it upto the equator. Study of the daily rawin trajectories of Madras and Trivandrum at intervals of 0. 5 kill upto 17 km shows that the axis ( core) of the easterly jet stream (altitude about 14.5 km) is nearer to Trivandrum in June and August and nearer Colombo in September. In July there is a broad band of high winds. It is found that in this region Trivandrum mean maximum wind is highest in all the months June to September, the maximum occurring generally at about 0.5 km higher at Madras than over Trivandrum and Colombo. Observations at Goa (Lat. 15° 29'N) have shown simultaneous existence of another speed maximum in the neighbourhood of Goa at about 16 km.